1983
DOI: 10.1080/07391102.1983.10507477
|View full text |Cite
|
Sign up to set email alerts
|

On the Processivity of DNA Replication

Abstract: In this paper we describe the nature and importance of processive enzymatic reactions in biological processes. A model is set up to describe the processive synthetic process in DNA replication, and experiments are presented to define and test the model, using the components of the T4 phage-coded five-protein (in vitro) DNA replication system of Alberts. Nossal and coworkers. These experiments are performed either with a homogeneous oligo dT-poly dA primer-template system, or with a natural primer-template syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…26; M.K.R., unpublished data). Furthermore, Bedinger et al (27), also using large circular viral templates, showed that T4 polymerase pauses at 4-residue palindromic sequences similar to the stop site demonstrated above.…”
Section: Resultsmentioning
confidence: 83%
“…26; M.K.R., unpublished data). Furthermore, Bedinger et al (27), also using large circular viral templates, showed that T4 polymerase pauses at 4-residue palindromic sequences similar to the stop site demonstrated above.…”
Section: Resultsmentioning
confidence: 83%
“…In this paper, we have shown that rapid and processive strand displacement leading-strand DNA synthesis can be achieved with a properly loaded and activated two-protein helicase-polymerase system. Yet it is also clear that under physiological salt conditions even minimal processive synthesis by polymerase alone on a single-stranded template requires participation of the gp44͞62 and gp45 accessory proteins (or their equivalents in other replication systems) to form and to load the sliding processivity clamp and thus to tether the polymerase (and the nascent DNA strand) onto the template (28)(29)(30)(31). More recently it has also been shown (26) that an essential role of the gp61 primase subunit is to equivalently tether and stabilize the hexameric gp41 helicase onto the DNA to form a primosome complex that is sufficiently stable to complete the replication of an entire T4 genome.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that this nonspecifically bound state of the DNA polymerase at the p-t DNA junction is thermodynamically similar to the binding state of the DNA polymerase on nonspecific DNAs (single-stranded or double-stranded), which (at physiological salt concentrations; see Ref. 42) represents a significantly less stable polymerase-DNA complex (K d ϭ 100 -240 nM; see top entries in Table II; see "Results").…”
Section: State 1 Represents a Nonspecific And Loosely Bound Interactimentioning
confidence: 91%